Experiences of healthcare providers from a working week during the first wave of the COVID-19 outbreak - Villa, Giulia; Dellafiore, Federica; Caruso, Rosario; Arrigoni, Cristina; Galli, Emanuele; Moranda, Dina; Prampolini, Loredana; Bascape, Barbara; Merlo, Maria Grazia; Giannetta, Noemi; Manara, Duilio Fiorenzo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work. The delivery of care to patients with COVID-19 enhanced many psychological issues among healthcare workers (HCWs), exacerbating the risk of burnout and compromising the efficacy and quality of services provided to patients. In this context, the peculiarities regarding professional roles in delivering care to patients with COVID-19 might reflect daily lived experiences that could impact psychological outcomes in specific professional groups. However, daily lived experiences considering different groups of HCWs have been poorly investigated, especially with a longitudinal qualitative study. Accordingly, our study aims firstly to longitudinally explore perceptions and experiences of HCWs about their daily working life during the initial COVID-19 outbreak, highlighting the specific lived experiences of physicians, nurses, radiology technicians, and healthcare assistants.Methods. A longitudinal qualitative content analysis was conducted to analyse the comments and quotations made on a daily diary lasting seven days by physicians, nurses, radiology technicians, and healthcare assistants during the first wave of the COVID-19 outbreak. According to Elo and Kyngäs recommendation, the data analysis process was developed in three main phases: preparation, organising, and reporting.Results. Four main generic categories emerged by data analysis: ‘Clinical practice in COVID-19 patients’; ‘The importance of relationship’; ‘Navigating by sight’; and ‘Good always pays off’. Several differences emerged from the sentences of the HCWs, which require further investigation.Conclusions. Understanding the profession-specific experiences of the involved HCWs in facing the challenges of the COVID-19 pandemic is key for boosting reflections, research, and actions to adequately support each professional group